2020
DOI: 10.3390/catal10060643
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CO2 Methanation Reaction in C1 Chemistry over a Highly Dispersed Nickel Nanocatalyst Prepared Using the One-Step Melt-Infiltration Method

Abstract: The Paris Agreement requires the world to put the best efforts to reduce CO2 emissions, due to the global warming problems. As a promising technology corresponding to this greenhouse gas treatment, the CO2 methanation process a.k.a power to gas (PtoG), which catalytically converts CO2 into methane, has been in the limelight. To develop an efficient catalytic process, it is necessary to design a low-cost and high-efficiency catalyst for high CO2 conversion and CH4 selectivity. In this study, we have developed N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Daroughegi et al [12] conducted CO 2 methanation experiments on Al 2 O 3 -supported Ni catalysts with different metal loadings, and the results revealed that the specific surface area and CO 2 conversion increased with an increase in the Ni loading from 15, 20, and 25 wt%, whereas the specific surface area and CO 2 conversion decreased at 33 wt%. In the study on Ni/γ-Al 2 O 3 , Cho et al [13] reported that the highest dispersion, CH 4 selectivity, and reaction rate were observed at 20 wt% Ni content when the Ni content was varied from 15 to 50 wt%.…”
Section: Introductionmentioning
confidence: 99%
“…Daroughegi et al [12] conducted CO 2 methanation experiments on Al 2 O 3 -supported Ni catalysts with different metal loadings, and the results revealed that the specific surface area and CO 2 conversion increased with an increase in the Ni loading from 15, 20, and 25 wt%, whereas the specific surface area and CO 2 conversion decreased at 33 wt%. In the study on Ni/γ-Al 2 O 3 , Cho et al [13] reported that the highest dispersion, CH 4 selectivity, and reaction rate were observed at 20 wt% Ni content when the Ni content was varied from 15 to 50 wt%.…”
Section: Introductionmentioning
confidence: 99%
“…9-12 CO 2 capture and recovery is an effective method to deal with the increasing greenhouse effect. [13][14][15] CO 2 methanation for producing hydrocarbons is one of the effective ways of converting waste into resources and energy to solve the problem of CO 2 emissions caused by environmental and energy crisis. [16][17][18][19][20] Besides, CO 2 methanation could be a good route for hydrogen storage and transportation, which could make full use of green hydrogen produced by renewable energy, such as solar energy or by industrial water gas reaction, 9,21,22 contributing to the further realization of a low-carbon society in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Daroughegi et al [12] conducted CO2 methanation experiments on Al2O3-supported Ni catalysts with different metal loadings, and the results revealed that the specific surface area and CO2 conversion increased with the increase in the Ni loading from 15, 20, and 25 wt%, whereas the specific surface area and CO2 conversion decreased at 33 wt%. In the study on Ni/γ-Al2O3, Cho et al [13] reported that the highest dispersion, CH4 selectivity, and reaction rate were observed at 20 wt% Ni content when the Ni content was varied from 15 to 50 wt%. Jaffar M.M et al [9] compared the activities of the 10 wt% Ni catalysts supported on SiO2, MCN, and Al2O3.…”
Section: Introductionmentioning
confidence: 99%